2016
DOI: 10.9734/ejmp/2016/22443
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening and Antimicrobial Activity of Crude Stem Bark Extracts of Anogeissus leiocarpus

Abstract: Aims: This study was aimed at screening of phytochemicals and evaluation of antimicrobial activity of stem bark of Anogeissus leiocarpus Study Design: Stem bark of Anogeissus leiocapus was extracted using solvent extraction method; with ethanol, n-hexane, chloroform, ethylacetate and water soluble extracts. Each extract was screened for phytochemicals and tested for sensitivity against E. coli and Shigella dysenteriae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
(14 reference statements)
1
3
0
Order By: Relevance
“…The results reported in our study agree with the study reported previously where saponins and flavonoids were detected [27]. In a similar study, flavonoids were detected in the ESBE of A. leiocarpus while alkaloids were absent which agrees with the present study [28]. Previous studies on phytochemical components of stem bark extracts of A. leiocarpus reported results similar to our study [29,30].…”
Section: Resultssupporting
confidence: 93%
“…The results reported in our study agree with the study reported previously where saponins and flavonoids were detected [27]. In a similar study, flavonoids were detected in the ESBE of A. leiocarpus while alkaloids were absent which agrees with the present study [28]. Previous studies on phytochemical components of stem bark extracts of A. leiocarpus reported results similar to our study [29,30].…”
Section: Resultssupporting
confidence: 93%
“…In the DPPH assay, the antioxidants are able to reduce the stable radical DPPH to nonradical form, DPPH-H. Various mechanisms have been put forward to explain the antioxidant activity of phenolic compounds including reducing capacity, prevention of chain initiation, binding of transition metal ion catalysts, decomposition of peroxides, prevention of continued hydrogen abstraction and radical scavenging (Vasanthi et al, 2014). The reducing capacity of a compound may serve as a significant indicator of its potential antioxidant activity (Chanda et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In other cases, the plant parts are ground to powder and applied to external wounds to prevent infection to allow the healing process to take place (23). In experimental studies, AL was reported to exhibit antihyperglycemic (24), antioxidant (24), antihyperlipidemic (24), and antimicrobial effects (25) through different modes of action attributed to its phytoconstituents including alkaloids, glycosides, and flavonoids. However, there are limited studies revealing the potential mechanisms of action…”
Section: (−)-mentioning
confidence: 99%